TESTING OF WHEAT GENOTYPES FOR SALT TOLERANCE AND LEAF RUST DISEASE CAUSED BY PUCCINIA - SAIFULDEEN SALIM; FIRAS ALDULAIMY; UTOOR ALDEEN (Innovare Journal of Agricultural Sciences, 2024)
Parameters that show a significant genotypic variation and are associated with salt tolerance may be used as rapid and economic screening criteria in breeding programs. The objective of this study was to test growth and yield components for evaluating the salt tolerance of wheat genotypes. Five genotypes of winter wheat (Triticum aestivum L.) were used in this study, that differ from their salt tolerance, which were grown in 28 dS/m saline soil, and irrigated by well water with a salinity 7.5 dS/m. The results showed that salt concentration in the soil was reduced with plant growth stages from 28 dS/m before sowing to 8, 7.5, and 7.6 dS/m for N1, N2, and N3 genotypes, respectively. Whereas approached 16 and 17 dS/m for Tumos2 and Mexipak, cultivars, respectively, at the maturity stage. Concerning germination percentage under saline conditions, wheat genotypes N1, N2, and N3 showed the highest percentages of 89, 90, and 90%, respectively, which was significantly different than wheat cultivars Tumos2 and Mexipak 79 and 83%, respectively. Statistical analysis of the data revealed that genotype N2 required a maximum days for germination 14 days, whereas cultivar Tumos2 required less days for germination 12 days. For spikes formation duration growth the genotype N3 was the late 119 days, whereas for physiological maturity N1 genotype was the latest 153 days. The number of spikes per 6 m2, grains spike-1, and grain weight were reduced significantly in sensitive cultivars Tumos2 and Mexipak. Higher grain yield with N2 genotype 2739.43 g with no significant differences with the genotypes N1 and N2, and with significant differences with the rest sensitive cultivars Tumos2 and Mexipak 346.61 and 242.98 g, respectively. Therefore, we conclude that the measurements of growth and yield components may be effective criteria for screening wheat genotypes for salt tolerance. Moreover, N1, N2, and N3 genotypes were identified as the most salt-tolerant genotypes in this study, they can be utilized through appropriate selection and breeding programs for further improvement in salt tolerance of Iraqi wheat genotypes.